2014
DOI: 10.1002/ps.3903
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference of the P450CYP6CM1gene has different efficacy in B and Q biotypes ofBemisia tabaci

Abstract: RNA interference of the P450 CYP6CM1 gene reduced gene expression, increased mortality, and inhibited the ability to detoxify a pesticide or a plant secondary metabolite in both biotypes of B. tabaci, with better efficacy in B biotype than in Q biotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 34 publications
(66 reference statements)
1
49
0
2
Order By: Relevance
“…tabaci and H . armigera , revealing no obvious correlation of increase of dsRNA concentrations with the degree of target mRNA knockdown [25,47]. …”
Section: Discussionmentioning
confidence: 99%
“…tabaci and H . armigera , revealing no obvious correlation of increase of dsRNA concentrations with the degree of target mRNA knockdown [25,47]. …”
Section: Discussionmentioning
confidence: 99%
“…For instance, through RNAi studies, several studies have shown that constitutive upregulation of CYPs mediates resistance to pyrethroid insecticides in the diamondback moth, Plutella xylostella 35 , the carmine spider mite, Tetranychus cinnabarinus 36 , and the red flour beetle, Tribolium castaneum 37 . Additionally, CYPs are involved in resistance to neonicotinoids in the small brown plant hopper, Laodelphax striatellus 38 and the tobacco whitefly, B. tabaci 39 , to organophosphates in the tobacco cutworm, Spodoptera litura 40 , and to abamectin in P . xylostella 41 .…”
Section: Discussionmentioning
confidence: 99%
“…RNA concentrations were determined using a spectrophotometer73 and sent to the Beijing Genomics Institute (BGI, Shenzhen, China) when TREs expression were inhibited by the way of RNAi.…”
Section: Methodsmentioning
confidence: 99%